2011
DOI: 10.1177/1073191111431341
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Racial Measurement Equivalence of the Eyberg Child Behavior Inventory Factors Among Low-Income Young African American and Non-Latino White Children

Abstract: This study examined the cross-racial measurement equivalence of the three Eyberg Child Behavior Inventory Intensity Scale factors, found by Stern and Johnson: Oppositional Defiant Behavior, Attention Difficulties, and Conduct Problems. Cross-racial measurement equivalence was examined between 278 low-income African American and 119 non-Latino White children aged 3 to 6 years. Results did not support configural equivalence of the three subscales between groups. Exploratory factor analyses conducted separately f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…In a clinically referred US sample of children between 4 and 16 year of age correlations between the ECBI Intensity Scale and the CBCL Externalizing Behavior scale were 0.75 (Boggs et al 1990 ). In line with the expectations, correlations with scales measuring internalizing behavior problems were lower than correlations with scales measuring externalizing behavior problems (Axberg et al 2008 ; Butler 2011 ). With regards to the discriminative validity of the ECBI, in the clinically referred US sample as described by Weis and colleagues ( 2005 ), the Intensity Scale distinguished between groups of children with no significant externalizing problems, children with inattentive and oppositional behavior symptoms, and children with more serious behavioral problems.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a clinically referred US sample of children between 4 and 16 year of age correlations between the ECBI Intensity Scale and the CBCL Externalizing Behavior scale were 0.75 (Boggs et al 1990 ). In line with the expectations, correlations with scales measuring internalizing behavior problems were lower than correlations with scales measuring externalizing behavior problems (Axberg et al 2008 ; Butler 2011 ). With regards to the discriminative validity of the ECBI, in the clinically referred US sample as described by Weis and colleagues ( 2005 ), the Intensity Scale distinguished between groups of children with no significant externalizing problems, children with inattentive and oppositional behavior symptoms, and children with more serious behavioral problems.…”
Section: Introductionsupporting
confidence: 73%
“…Gross et al ( 2007 ) found more support for the validity of the ECBI as a one-dimensional measure for child behavioral problems. More recently, in a community sample, including low income families from different cultural backgrounds and of different ethnicities Butler ( 2011 ) failed to replicate the results for a three-factor structure of the ECBI and suggested that these factors are not used for screening and treatment outcome research.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of construct validity, although developed as a unidimensional instrument, recently it has been suggested that the inventory measures three distinct clusters of behavior, namely 1) oppositional defiant behavior towards adults, 2) inattentive behavior, and 3) conduct problem behavior (Axberg et al 2008 ; Weis et al 2005 ). This three factor structure was indeed replicated in several studies (e.g., Burns and Patterson 2010 ), but not found in others (e.g., Butler 2013 ; Gross et al 2007 , including in a Dutch sample by Abrahamse et al 2015 ). For example, Gross et al ( 2007 ) found more support for the validity of the ECBI as a one-dimensional measure for child behavioral problems.…”
mentioning
confidence: 68%
“…The internal consistencies for the Intensity and Problem Scales are .93 and .98, respectively (Eyberg, 1999). Adequate internal consistencies have been reported for African-American and Latino children (Butler, 2013; Gross et al, 2007). …”
Section: Methodsmentioning
confidence: 99%